The traveler and the researcher (Palíndromo, 2016)
This paper is about the academical trajetory being discussed as a metaphore of the traveling and of the traveler. While is done an analysis of Sandra Makowie- cky’s thesis and of his own   research, the author thinks about the experience of Marguerite Duras and other resear- chers, which texts are found in the book “The compass of writing”. The same ar- tists selected by Sandra in her thesis are discussed here as references of the own experiences of building of a thesis/ dis- sertation.
Keywords: travel; traveler; city; research; thesis